Dora Bruder and the Longue Durée - Susan Weiner (Studies in 20th & 21st Century Literature, 2007)
Modiano's methods in Dora Bruder recall the Annales historiographer's rejection of the history of events in favor of the "long duration," but with human history as its object. Modiano's long duration draws out repetitions and variations between his own life and Dora's as he reconstructs and imagines it, between Dora and fictional characters, between Dora's story and the lives of Holocaust victims and survivors known and unknown. Moreover, the author encourages the reader to take part in the uncanny connections the novel makes, through movements of the imagination not unlike Modiano's own. In so doing, we approach Dora and those who shared her fate through their lives rather than their death, restoring to them the everyday freedom of their thoughts and actions alongside our own.
Keywords: Patrick Modiano; Dora Bruder; long duration; history; personal history; Holocaust victims; Holocaust survivors; Holocaust